Characterization of L-Lysine-A-Oxidase, A New Antitumor And Antiviral Drug Substance Synthesized By Trichoderma: Life Sciences-Chemical - Smirnova, I.P.; Kuznetsov, V.I.; Podoprigora, I.V.; Mansur, T.I.; Senyagin, A.N.; Bashkirova, I.G. (International Journal of Life Science and Pharma Research, 2022)
The trigger to the studies of L-lysine-a -oxidase is of great interest for the scientists across the world. Regarding Russian Federation, the enzyme is under examination by several laboratories. Attracted by the polyfunctionality of the enzyme, the likelihood of utilizing this substance in the creation of multiple dosage forms of different therapeutic orientation. Thus, the main aim of the study is to analyze the new characteristics of L-lysine-a -oxidase as a new antitumor and antiviral drug substance synthesized by Trichoderma. To meet the study’s aim, a biological experiments were carried out on guinea pigs weighing 200-250 g and CBA mice (CBA x C57BI) weighing 18-20 g, C57 Bl, SHR.Native L-lysine-a -oxidase was injected into C57BI mice five times intravenously at a dose of 35 U/kg. Blood was sampled every week for four weeks from the beginning of immunization (n=7), and the obtained sera of mice were analyzed by enzyme-linked immunosorbent assay according to a previously developed method. The sera were titrated in increments of 2. Tests of L-lysine-a -oxidase in mice and guinea pigs found low immunogenicity of Llysine- a -oxidase when administered in mice at a dose of 35 U/kg, or 0.8 ml of protein/kg. Based on the results obtained, antibodies not only reduce its catalytic activity but also affect the affinity of the enzyme with the substrate. Experiments on guinea pigs have shown that native and modified L-lysine-a -oxidase at a dose of 35 U/kg in vivo and in vitro has a low allergenic activity. The allergenic activity of L-lysine-a -oxidase was investigated in comparison with other drugs. The results od this article, can be considered as one of a brand-new and effective methods for assessing the body sensitization caused by the use of enzymes and can contribute to the development of the respective field.